Disease burden contributed by dietary exposure to aflatoxins in a mountainous city in Southwest China - Qin, Mei; Cheng, Li; Li, Yan; Tang, Xiaoqin; Gan, Yuan; Zhao, Jian; Luo, Shuquan; Zhang, Huadong; Zhang, Lishi; Chen, Jinyao; Huo, Jiao (Frontiers in Microbiology, 2023)
Introduction Aflatoxins (AFT) identified as a Group 1 human carcinogen naturally contaminate various types of food and could increase the risk of hepatocellular carcinoma (HCC) through dietary intake. Chongqing municipality is located in Southwest China with subtropical monsoon climate which is conducive to AFT contamination in crops. However, the burden of HCC caused by the dietary exposure of the population in Chongqing to AFT has not been quantified. Methods The burden of HCC was estimated in terms of Disability Adjusted Life Year (DALY) using FDA-iRISK software. Dietary exposure to AFT in three food categories including grain and its products, nuts and seeds, and spices was assessed. Results The lifetime average daily dose (LADD) of AFT exposure for the population ranged from 2.40 to 8.25 ng/kg bw/day and 9.51 to 15.10 ng/kg bw/day at the mean and heavy (P95) AFT contamination levels, respectively. Among the three food categories, grain and its products contributed most to AFT exposure of the population. The estimated DALYs related to HCC induced by AFT were 162,000–556,000 and 641,000-1,020,000; the DALY rates were 6.47–22.20 and 25.59–40.72 per 100,000 persons per year; and the population attribution fractions (PAF) were 1.68–5.78% and 6.66–10.60%. Discussion Although the burden of HCC caused by dietary AFT was estimated to be relatively low among the population, the overall health burden might be underestimated owing to the uncertainties of this dataset. Thus, the overall health burden associated with AFT intake should still be of concern in further studies.